Field evaluation of mungbean varieties for resistance against pod borer complex - Ullah, M H; Khan, M M H; Pinke, U H; Ashik, M H (Jahangirnagar University Journal of Biological Sciences, 2024)
Field experiment was carried out at farmer’s field in Sonakhali, Barguna sadar, Barguna to evaluate the resistance sources(s) among different verities of mungbean against the pod borer complex during the period from January to April 2016. Ten varieties viz., BARI Mung- 2, BARI Mung- 5, BARI Mung- 6, BU Mung- 1, BU Mung- 2, IPSA Mung- 5, IPSA Mung- 12, GK Mung- 27, BINA Mung- 2 and local Mung were included in the study. The variety of BARI Mung- 6, local Mung, BARI Mung- 5 and GK Mung- 27 had the highest population of Maruca which indicated that these varieties were highly susceptible to Maruca while BINA Mung- 2, BARI Mung- 2, IPSA Mung- 5 and IPSA Mung- 12 had lowest population of Maruca which indicated that these varieties were least susceptible to Maruca. Among all tested varieties, none showed complete resistance against Maruca. From the mean of all varieties regarding Helicoverpa population, BARI Mung- 6, Local Mung, IPSA Mung-12 and IPSA Mung- 5 had the highest population of Helicoverpa which indicated that these varieties were highly susceptible to Helicoverpa while BARI Mung- 5, BU Mung- 1, GK Mung- 27 and BINA Mung- 2 had lowest population of Helicoverpa which indicated that these varieties were least susceptible to Helicoverpa. Among all tested varieties, none showed complete resistance against Helicoverpa. BU Mung- 1 and BINA Mung-2 showed comparatively better resistance against Maruca and BARI Mung- 2 and BU Mung- 2 showed comparatively better resistance against Helicoverpa. The highest total yield was obtained from BARI Mung- 6 followed by BARI Mung- 5 and the lowest total yield was obtained from BARI Mung- 2 followed by the GK Mung- 27. BARI Mung- 6 and BARI Mung- 5 appeared to be the best varieties in terms of resistance against pod borer complex and yield. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 97-105, 2023 (June & December)